Analysis of fuel pressure on the performance of motorcycle engine with ethanol fuel. Issue 1 (February 2021) - Irawan, B; Winoko, Y A; Puspitasari, E; Dwiyono, T
Abstract: Gasoline engines fuel cannot be directly replaced with pure ethanol, moreover ethanol contains a lot of water. The purpose of the study was to analyze the effect of fuel pump pressure on performance of 4-stroke engine motor cycle by ethanol fuel. The independent variable is pressure of the fuel and the engine speed. The dependent variable is the engine power, torque, and specific fuel consumption. The power and torque test use inertia dynamometer. The results showed the addition of fuel pump pressure, at 3.5 bar pressure can produce higher power at each engine speed with a maximum power of 6 HP at 8000 rpm. As for the best results torque obtained at a pressure of 3.5 bar which is 5, 5 Nm at 7500 rpm, besides that the lowest specific fuel consumption SFC at a pressure of 3, 5 bar is 0.409 kg/HPh. The results of this study can be concluded that gasoline vehicles can use ethanol fuel by increasing the fuel pressure up to 3.5 bar.